2018
DOI: 10.1177/0269216318758212
|View full text |Cite
|
Sign up to set email alerts
|

The use of behavioural theories in end-of-life care research: A systematic review

Abstract: In end-of-life care research, the use of behavioural theories is limited. As many behaviours can determine the quality of care, their more extensive use may be warranted if we want to better understand and influence behaviours and improve end-of-life care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 61 publications
1
34
0
Order By: Relevance
“…Whilst people with breast cancer require support, especially those with advanced cancer (47), so too do people with other diagnoses. Studies reviewed are mostly not underpinned by any form of theory, a trend also identified in a recent review of behavioural theories in end-of-life care research (48). Peer support intervention descriptions were often poor, it was challenging to extract details from many included papers, such as understanding the intervention at 'Cairn Centres' (25), the use of former patients (27), or the form and function of some groups (34).…”
Section: Comparison With Previous Reviewsmentioning
confidence: 99%
“…Whilst people with breast cancer require support, especially those with advanced cancer (47), so too do people with other diagnoses. Studies reviewed are mostly not underpinned by any form of theory, a trend also identified in a recent review of behavioural theories in end-of-life care research (48). Peer support intervention descriptions were often poor, it was challenging to extract details from many included papers, such as understanding the intervention at 'Cairn Centres' (25), the use of former patients (27), or the form and function of some groups (34).…”
Section: Comparison With Previous Reviewsmentioning
confidence: 99%
“…11 Bandura's 12 theory has been used as a model to evaluate relationships between knowledge, self-efficacy and behaviour in research regarding health promotion, palliative care and recently in research regarding patients' readiness to engage in advance care planning. [13][14][15][16] We know that knowledge about advance care planning is associated with self-efficacy and vice versa. 8,17 However, our understanding whether and to what extent these constructs also relate to professionals' engagement in actual advance care planning practices is incomplete.…”
Section: Introductionmentioning
confidence: 99%
“…The practicebased design of ACP conversation guides complicates the understanding of the communicative process and illustrates the need for research to reveal underlying communicative, relational, and behavioral principles. 101,102 Our review shows there is a large body of existing interventions. The growing interest in ACP should therefore not result in the development of more new interventions, but in deeper evaluation of current strategies to understand which (components of) ACP interventions are effective and why.…”
Section: Resultsmentioning
confidence: 99%